Improving Your Splunk Skills Leverage the Operational Intelligence Capabilities of Splunk to Unlock New Hidden Business Insights - D. Miller, James (Packt Publishing, Limited, 2019)
This Learning Path is your comprehensive guide to making machine data accessible across your organization using advanced dashboards. With over 80 realistic examples, you'll get several recipes to use Splunk and transform your data into business-critical insights.